Stability And Predictive And Incremental Accuracy Of The Individual Items Of Static-99r And Static-2002r In Predicting Sexual Recidivism: A Meta-Analysis. (September 2015) - Helmus, Leslie-Maaike; Thornton, David
This study investigated a potential source of variability in actuarial scale performance: the individual items. Using data from 8, 053 sex offenders across 22 samples, we examined the predictive and incremental accuracy of the items from Static-99R and Static-2002R, and the stability of predictive accuracy across samples. Generally, all items had significant predictive accuracy and contributed incrementally to predicting sexual recidivism, with few exceptions. Roughly half the items demonstrated significant variability in their predictive accuracy across samples, although this was often variability in the magnitude of predictiveness as opposed to the direction. Some moderator effects were found, with the most common being the country of the study (which influenced accuracy in different directions depending on the item) and whether the offenders were preselected as unusually high risk or need (lower discrimination was found in these samples). The findings support the Static-99R and Static-2002R items with few exceptions, and possibilities for future research are highlighted.